(untitled) (American Journal of Technology and Applied Sciences, 2024)
The development of social infrastructure in the world serves to increase the well-being of the population, for this the state is responsible for solving urgent tasks. In the era of rapid urbanization in the world, along with the development of infrastructure, the issue of improving the livelihood of rural people is among the highest goals.